Mixed-Numerology Channel Division for Wireless Avionics Intracommunications. (26th April 2022) - Fan, Xianghui; Li, Shining; Cui, Wen; Yang, Pu; Chen, Changsheng; Huang, Guan-Long
Abstract : Increasing attention has been paid to the wireless avionics intracommunications (WAIC) on aircraft. The frequency band of 4200-4400 MHz is recommended to WAIC by the International Telecommunication Union Radio Communication Sector (ITU-R), which thereby comes with a new challenge of using the available frequency band effectively to cater for the massive communication needs in aircraft. To address this challenge, we propose the first channel design framework named mixed-numerology channel division (MNCD) specifically for WAIC. Furthermore, a general interference model has been proposed to better utilize the recommended frequency band. Extensive evaluations show that the proposed framework can be a promising solution for massive wireless communications in aircraft.